SPECTRAL APPROACH TO DEVELOPMENT SYNTHESIS ON THE BASIS OF INHOMOGENEOUS LINES AND ISSUES OF DETERMINING WAVE RESISTANCE ACCORDING TO THE CENTRAL PART OF LEAKAGE INFORMATION CHANNELS (REVIEW) - Приходько, Т. Ю.; Басюк, І. О.; Ліщиновська, Н. О. (Science-based technologies, 2019)
One of the methods to prevent information leakage is filtering, which is carried out in order to prevent the propagation of high-frequency information signals outside the controlled area. To filter the signals in the power supply circuits, noise suppressing low-pass filters (LPF) are currently used. It is established that information leakage channels are determined by the location of the zeros and poles of the input impedance of the line on which the filter is based. In this case, two situations are possible: when building a filter, it is possible to change the zeros and poles of both the input resistance of the open circuit and the closed line. The set of zeros and poles consists of resonance and resonance frequencies that form the spectrum of the line. The procedure for increasing the frequency band of the barrier of distributed low-pass filters (LPF) due to the use of non-uniform (irregular) segments of transmission lines as filter sections is considered. This task has many solutions, one of which is the finding of such a function of wave impedance change from the line coordinate, for which there are no information leakage channels (parasitic channels) in a given frequency band. As a result, it is possible to obtain a significant gain in the discharge of the spectrum of resonant frequencies, improve the selective properties, suppress spurious bandwidths, and make technological nodes, the realization of which on the basis of homogeneous lines would be impossible. The considered techniques can be used to develop methods for constructing filters with a given distribution of information leakage channels by shifting the zeros and poles of the input resistance and to obtain analytical expressions for determining the wave resistances of multi-step lines with the required number of steps, which allows determining wave resistances filter step